CFStrace: An evaluation method to include complex fenestration systems in the façade design process. (15th March 2021) - Mashaly, Islam A.; Garcia-Hansen, Veronica; Isoardi, Gillian; Cholette, Michael E.
Graphical abstract: Highlights: CFS assessment is a complicated process that building designers tend to avoid using. A simple CFS assessment framework is developed using a new tool CFStrace. It introduces metrics to predict light uniformity ensuring adequate visual comfort. The new framework generates fast daylight analysis results to select a suitable CFS. Abstract: Complex fenestration systems (CFS) have proven to enhance the daylight quality inside spaces when designed correctly. While research in this area focuses on assessing CFS performance accurately, the number of CFS daylight analysis frameworks are too complex for the building designer to use for selecting a suitable CFS. Also, some CFS design frameworks focus only on light redirection efficiency without considering the spatial or environmental context. The paper demonstrates a new framework to analyse CFS considering both architectural and environmental conditions. The framework is presented as a computational tool (CFStrace), which accepts parametric geometric input and uses forward raytracing to simulate the complex optical behaviour of CFS. The framework also introduces new metrics for the assessment of CFS, which are developed to suit the forward raytracing simulation technique, that predicts the uniformity of redirected sunlight in the built environment and ensures adequate visual comfort to the occupants. A comparison study is carried out to state the effectiveness of the metrics where various CFS designs from previous literature are tested. The comparative case study revealed which CFS designs would be more suitable at the specific setting and location and provided insight on metrics that can be used to assess the feasibility of one design over the other in terms of daylight performance. The new framework will involve less technical and modelling capabilities making it "architect-friendly" encouraging building designers to include CFS in their design process, especially in the early design phase, and pave the way for new CFS designs possibilities.